2015
DOI: 10.1179/1743281214y.0000000261
|View full text |Cite
|
Sign up to set email alerts
|

Is low phosphorus content in steel a product requirement?

Abstract: An attempt is made, on the basis to published literature, to assess the amount of phosphorus that might be present in the steels without making it susceptible to grain boundary embrittlement. Embrittlement occurs when the general resistance to plastic flow is comparable to the stress required to separate crystals at their boundaries. A criterion is developed that enables a simple assessment to be made of the tendency to embrittle as a function of yield strength and the fraction of grain boundary sites that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…An increase in slag basicity usually helps to control the content of inclusion like sulfur and phosphorus in hot metal and steel, respectively, but various other factors also affect the same. [38][39][40] The carbon dissolution in the metallic droplets is somewhat related to the extent of reduction as mentioned earlier. However, factors like carbon distribution in the melt along with the presence of other elements and oxides do affect the phenomenon of carbon pickup.…”
Section: Microstructural Analysismentioning
confidence: 74%
“…An increase in slag basicity usually helps to control the content of inclusion like sulfur and phosphorus in hot metal and steel, respectively, but various other factors also affect the same. [38][39][40] The carbon dissolution in the metallic droplets is somewhat related to the extent of reduction as mentioned earlier. However, factors like carbon distribution in the melt along with the presence of other elements and oxides do affect the phenomenon of carbon pickup.…”
Section: Microstructural Analysismentioning
confidence: 74%
“…Some alloying elements such as Titanium, Niobium, Molybdenum, and Vanadium show efficacy in mitigating Phosphorus concentration on grain boundary [ 8 ]. It is suspected that a few mechanisms contribute to that, such as Ti and Nb “pinning” P inside of the matrix or settling on the grain boundary themselves, thus restricting the amount of space Phosphorus can take up [ 39 ]. However, the exact effects are difficult to quantify, especially since all those elements show the ability to form carbides [ 33 ], limiting their anti-embrittlement effect.…”
Section: Methodsmentioning
confidence: 99%
“…With this number of overlapping effects in play, it is incredibly challenging to determine a “safe” amount of Phosphorus in respect of temper embrittlement [ 39 ]. Thus, restricting the overall number of impurities seems to be a better solution, especially nowadays, with modern advances in metallurgy.…”
Section: Methodsmentioning
confidence: 99%
“…Silicon can increase the carbon content in retained austenite by hindering the precipitation of cementite, which can have beneficial effects on toughness: however, it has a strong tendency to segregate to grain boundaries and reduce toughness [32,33]. It has been widely reported that, in medium-carbon low-alloyed steel especially after tempering, a significant increase in toughness can be obtained with Si contents below 0.30 wt.% [34,35].…”
Section: -2-silicon Contentmentioning
confidence: 99%